(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This paper This conceptual paper centered within the framework and directions of digital transformation in the field of university mentoring, and presented many methodologies, tools, practices and previous studies, as our main objective has been achieved that we have come to the conclusion that there is a need for a comprehensive and effective smart system for university mentoring, linked to skills, tendencies, market trends, and the compass that Future knowledge is heading towards it, as through our benchmark that we have made, we can confirm now that the existence of an application and a smart platform for academic and vocational guidance is very necessary not only for Al-Zaytoonah University, but for universities and the educational and academic system as a whole, because there is a great importance in ensuring the quality of Universities inputs and the quality of their outputs to the vocational market. Where this paper came as a link between the theoretical framework of our project, which we are currently working on at Al-Zaytoonah University of Jordan, and the next practical framework, which will be designed according to a technical and educational map with an entrepreneurial and innovative dimensions, through realistic simulation and applied modeling and Techniques.